Social Representation of Acupuncture: a Qualitative Study Among Young-Adult Cancer Survivors - Prabu Nusantara (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
Cancer prevalence in Indonesia presents a substantial challenge to healthcare, particularly affecting the young-adult demographic. As survival rates improve due to advancements in treatment, the long-term quality of life (QOL) for survivors becomes increasingly paramount. This qualitative study explores the social representation of acupuncture among young-adult cancer survivors in Jakarta, analyzing its role in managing persistent side effects post-treatment. In-depth interviews with five survivors reveal acupuncture as a multifaceted intervention perceived as less invasive and more aligned with natural bodily processes compared to conventional therapies. Findings indicate that acupuncture is not only employed to alleviate physical symptoms such as pain and fatigue but also to address psychological and cognitive repercussions, including depression, anxiety, and PTSD. Furthermore, acupuncture is appreciated for its cultural resonance within the Indonesian context, offering a sense of balance and well-being. Despite its less prominent role as an alternative therapy, acupuncture provides a sense of empowerment and control, enhancing adherence to treatment protocols and potentially improving survival outcomes. The study concludes that acupuncture represents a critical element of post-cancer care, advocating for an integrated, patient-centered approach that incorporates complementary and alternative medicines to support the comprehensive needs of cancer survivors. However, the study's scope is limited to a small sample size and a single urban setting, which may affect the generalizability of the findings. Further research is needed to validate these results in broader populations and diverse contexts.